AB0785 Incidence and treatments of digital and non-digital ulcers in 86 systemic sclerosis patients. (23rd January 2014) - Nitsche, A.; Amitrano, C.; Pucci, P.; Lescano, A.; Espíndola Echazú, M.; Seleme, G.M.; Molina, M.J.
Abstract : Background: Digital ulcers (DU) occur in nearly more than half of the patients with systemic sclerosis (SSc). Non-digital ulcers (legs) have also been described in SSc patients. DU are usually multiple, painful and if they are not treated rapidly, infections and hospitalizations are frequent. DU causes different degrees of disability with high impact in daily activities.Treatment is often insufficient. Objectives: To evaluate the incidence and treatments of DU, non–DU and digital tissue loss in SSc patients Methods: A transversal study. We analyzed the medical charts of 86 SSc patients. Four patients with morphea were excluded. Patients signed inform consent. We considered: diffuse or limited SSc, presence of Raynaud, ulcer type(digital or non digital), ulcer status(healed, active), digital tissue loss, and treatments. Results: Of 82 patients, 76 (92.7%) were female; mean age 53.9±13.9 years; mean evolution time of 7.2±6.0 years. Diffuse SSc (dSSC) was diagnosed in 56 (68.3%) patients and limited (lSSc) in 26 (31.7%). Raynaud was a manifestation referred by 97.8% of the patients with a mean evolution time of 11.1±9, 6 years. 46 of 82 patients (56.1%) had ulcers: 43 had DU and 3 had leg ulcers (without DU). Pulmonary arterial hypertension (PAH) was screened in 64 patients by colour Doppler echocardiogram (PAH was confirmed in 15 patients by RHCT). 18 of 34 patients with DU and 13 of 31 patients without DU had high levels of PASP. DU status in 46 patients:healed in 27 patients (58.7%); active DU in 24 patients (52.2%); digital tissue loss in 19 patients (41.3%). 18 patients (39.1%) had more than one type of lesion (active+healed+digital tissue loss). At the time of our evaluation, 12.5% of patients with active ulcers received no treatment, 29.1% received only one drug but at low doses and without dose escalation (calcium channel blockers or sildenafil or aspirin or cilostazol), 12.5% two, 37.5% three and 8.3% four drugs. Only 7 of the 19 patients under DU treatment received bosentan. Three of the seven patients with bosentan had leg ulcers. All the patients with DU, active or healed had diverse degrees of disability in their hands. One patient was hospitalized because of multiple DU Conclusions: DU in SSc patients are frecuent. A rapid step up treatment algorithm and at full doses is needed to avoid tissue loss, disability and hospitalizations. References: Natural history of ischemic digital ulcers in systemic sclerosis: single-center retrospective longitudinal study. Hachulla E, Clerson P, Launay D, et al. J Rheumatol 2007;34:2423-30 Digital ulcers: overt vascular disease in systemic sclerosis. Steen V, Denton CP, Pope JE, et al Rheumatology 2009; 48 (Suppl 3): 19-24 EULAR recommendations for the treatment of systemic sclerosis: a report from the EULAR Scleroderma Trials and Research group (EUSTAR). Kowal-Bielecka, Landewé R, Avouac J, et al. Ann Rheum Dis 2009; 68: 620-628 Disclosure of Interest: None Declared